1972
DOI: 10.1577/1548-8659(1972)101<483:rpotbb>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Potential of the Black Bullhead, Ictalurus melas, in Clear Lake, Iowa

Abstract: Gonadal development, time of spawning, and fecundity of black bullheads were examined in 1969 and 1970 for insight into the reproductive potential of this species in a warm-water lake. Maturity indexes peaked around 1 June in both years. Spawning was evidently triggered by rising water temperatures during June. Fecundity seemed unrelated to body length because ovaries of fish of similar length varied more than 100% in number of mature ova present. INTRODUCTION The black bullhead, Ictalurus melas, is an extreme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

1977
1977
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 0 publications
1
14
0
Order By: Relevance
“…We found the fecundities to be similar, however, to those of black bullheads (Ictalurus melas Rafinesque) (Dennison and Bulkley 1972). The bullhead eggs had a mean diameter of 2.17 mm and a mean weight of 0.005 g. No relationship was found between fecundity and length or weight, which also corresponds with findings for black bullheads (Dennison and Bulkley 1972).…”
Section: Resultssupporting
confidence: 78%
“…We found the fecundities to be similar, however, to those of black bullheads (Ictalurus melas Rafinesque) (Dennison and Bulkley 1972). The bullhead eggs had a mean diameter of 2.17 mm and a mean weight of 0.005 g. No relationship was found between fecundity and length or weight, which also corresponds with findings for black bullheads (Dennison and Bulkley 1972).…”
Section: Resultssupporting
confidence: 78%
“…Mean relative fecundity for European black bullhead ranges from 25.1 in Slovakia (Tisa oxbows) to 221.4 in England (Tom's Pond), with an overall mean of 99.6 (Copp et al., ). These values are significantly higher than those for native populations, which range from 5.5 (Dennison & Bulkley, ) to 18.8 (Maddux, ). Based on these results, Copp et al.…”
Section: Discussionmentioning
confidence: 70%
“…In addition to early maturation, fecundity also increased in the Lake Sava population following the mass mortality event, with absolute fecundity ranging from 1,702 to 4,447 (mean 2,896) in 2011, and 16,88 to 12,073 (mean 3,927) in 2012. In comparison, absolute fecundity of specimens from the River Váh (Slovakia) ranged from 1,238 to 4,755 (mean 2,610) (Novomeská & Kováč, ), while those for North American populations ranged from 2,047 to 5,495 in Iowa (Dennison & Bulkley, ), 2,552 to 3,372 in Kentucky (Campbell & Branson, ), and 2,550 to 3,850 in Virginia (Jenkins & Burkhead, ). A review of growth and life‐history traits in European black bullhead populations (Copp et al., ) indicated that absolute fecundity ranges from 1,251 to 7,975 (mean 4,446), being slightly (but not significantly) higher than that for native populations (2,155‐6,820, mean 3,609).…”
Section: Discussionmentioning
confidence: 99%
“…It was also coincident with a relatively high mean air temp of 18.3°C (Central England Temperature; Meteorological Office, ). In its native range, A. melas spawning tends to occur at temperatures of 21°C (Dennison and Bulkley, ), whilst in their invasive range, Novomeská and Kováč () suggested spawning in Slovakian oxbow lakes occurs at 18 to 22°C. Thus, temperature was not an inhibitor of A. melas reproductive success during our study period and so is unlikely to explain their inability to be invasive in the UK more generally.…”
Section: Discussionmentioning
confidence: 99%